Implementing of Risk Management on the Public Appraisal Service Office (KJPP) Febriman Siregar - Agung Prasetyo, Miko; Pompong B. Setiadi; Sri Rahayu (Dinasti International Journal of Economics, Finance & Accounting, 2022)
The work of the Public Appraisal Service Office employees who are mostly in the field to meet audit candidates makes them also often receive rejections. Prolonged psychological and physical fatigue will be a challenge faced by employees. To deal with these conditions, it is important for an employee to have Risk Management in dealing with situations in the field. In doing so, we contribute to the debate in recent research on Risk Management which conceptualizes it as a series of proactive and countermeasures that employees undertake to deal with work events and uncertainties and which are linked to important organizational-level performance indicators, such as increased well-being and productivity. Thus, the context of the Public Appraisal Service Office Employees as marketers of the Public Appraisal Service Office company is a very suitable background to explore the results of the HR development strategy as an adaptive process that promotes the first individual level Risk Management which ultimately leads to team Risk Management.